2017
DOI: 10.1264/jsme2.me17099
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation Mutants of the Actinobacterium <i>Frankia Casuarinae</i> CcI3

Abstract: Frankia is a representative genus of nitrogen-fixing (N2-fixing) actinobacteria; however, the molecular mechanisms underlying various phenomena such as the differentiation of a N2 fixation-specific structure (vesicle) and the regulation of N2 fixation (nif) genes, have yet to be elucidated in detail. In the present study, we screened hyphal fragments of Frankia casuarinae that were mutagenized by 1-methyl-3-nitro-1-nitrosoguanidine or gamma rays, and isolated 49 candidate N2 fixation mutants. Twelve of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…5 and Table S1). Genome analyses revealed that three of the mutants (G23C4, N7C9, and N10E6) did not carry mutations in these homologs (Kucho et al, 2017). Collectively, these results indicate that the genes responsible for the phenotypes of the three mutants are not related to global nitrogen regulation, but specifically function in the vesicle differentiation process (Fig.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…5 and Table S1). Genome analyses revealed that three of the mutants (G23C4, N7C9, and N10E6) did not carry mutations in these homologs (Kucho et al, 2017). Collectively, these results indicate that the genes responsible for the phenotypes of the three mutants are not related to global nitrogen regulation, but specifically function in the vesicle differentiation process (Fig.…”
mentioning
confidence: 75%
“…We previously isolated five N 2 -fixation mutants of Frankia casuarinae (G21E10, G23C4, G23D3, N7C9, and N10E6), which had smaller numbers of vesicles (<ca. 15% of the wild type) (Kucho et al, 2017) (Table S1). These mutants are considered to have defects in the generation of vesicle primordia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, a few studies on spontaneous mutants in Frankia spp. have been reported (11)(12)(13), and chemical (N-methyl-N-nitro-N-nitrosoguanidine and ethyl methanesulfonate treatments) and physical (UV) mutagenesis approaches have also been investigated with some success but limited potential as tools (14)(15)(16)(17).…”
mentioning
confidence: 99%